“Parliamentary sovereignty rests with the courts:” The Constitutional Foundations of J. G. Diefenbaker’s Canadian Bill of Rights - Birenbaum, Jordan Daniel (Université d'Ottawa / University of Ottawa, 2012)
The 1980s witnessed a judicial “rights revolution” in Canada characterized by the Supreme Court of Canada striking down both federal and provincial legislation which violated the rights guaranteed by the 1982 Charter of Rights. The lack of a similar judicial “rights revolution” in the wake of the 1960 Canadian Bill of Rights has largely been attributed to the structural difference between the two instruments with the latter – as a “mere” statute of the federal parliament – providing little more than a canon of construction and (unlike the Charter) not empowering the courts to engage in judicial review of legislation. Yet this view contrasts starkly with how the Bill was portrayed by the Diefenbaker government, which argued that it provided for judicial review and would “prevail” over other federal legislation. Many modern scholars have dismissed the idea that the Bill could prevail over other federal statutes as being incompatible with the doctrine of parliamentary sovereignty. That is, a bill of rights could only prevail over legislation if incorporated into the British North America Act. As such, they argue that the Diefenbaker government could not have intended the Bill of Rights to operate as anything more than a canon of construction. However, such a view ignores the turbulence in constitutional thinking on parliamentary sovereignty in the 1930s through 1960s provoked by the Statute of Westminster. This era produced the doctrine of “self-embracing” sovereignty – in contrast to traditional “Dicey” sovereignty – where parliament could limit itself through “ordinary” legislation. The effective author of the Canadian Bill of Rights, Elmer Driedger, was an adherent of this doctrine as well as an advocate of a “purposive” approach to statutory interpretation. Driedger, thus, drafted the Bill based upon the doctrine of self-embracing sovereignty and believed it would enjoy a “purposive” interpretation by the courts, with the Bill designed to be as effective at guaranteeing rights as the Statute of Westminster was at liberating Canada from Imperial legislation.
Keywords: Elmer Driedger; Canadian Bill of Rights; bill of rights; human rights; Diefenbaker; Department of Justice; parliamentary sovereignty; self-embracing sovereignty; implied bill of rights; parliamentary supremacy; British North America Act; constitutional amendment; Statute of Westminster; Edmund Fulton; judicial review; Supreme Court of Canada